Filling the 'Gaps' in the Representation of Australia's Cultural Diversity: The Multicultural Imaginary of the NLA's Oral History Collection. Issue 1 (2nd January 2022) - Boyd, Jodie
ABSTRACT: In Australia's National Library, the acquisition or commissioning of oral histories is accepted as a method by which their representative mission as socially inclusive and culturally diverse institution can be fulfilled. In this goal, oral history projects which focus on underdocumented, minoritised or marginalised individuals, groups or communities commonly stake their value on the claim that such projects can work to fill the 'gaps' in the national story, contribute to a more complete historical record, or recover lost, overlooked or hidden histories. Drawing on the NLA's institutional documentation, this paper develops the findings of an empirical examination of the NLA's oral history collection. This examination found a significant mismatch between representations of the oral history collection as diverse and the actual number of 'diverse' interviews. Using the analytic lens provided by critical librarianship, this paper considers the implications of these findings and argues for greater recognition of the culturally positioned nature of oral history methodology. It is suggested that by re-thinking oral history's neutrality, space might be found within collections for a diversity of oral literacies and 'unique epistemologies ways of knowing, languages, and histories'.